Experimental investigation of a process chain combining sheet metal bending and laser beam melting of Ti-6Al-4V - Butzhammer, Lorenz; Dubjella, Patrick; Huber, Florian; Schaub, Adam; Aumüller, Markus; Baum, Alexander; Petrunenko, Oleksandra; Merklein, Marion; Schmidt, Michael (Lasers in Manufacturing LIM 2017, 2017)
In spite of several advantages such as a great freedom of design, comparatively long process times are a major drawback in additive manufacturing technologies such as laser beam melting (LBM) of metal powder. A strategy to overcome this limitation is to combine additive manufacturing with other promising manufacturing concepts. In this paper, we characterize hybrid components manufactured using a consecutive process chain including warm bending of Ti-6Al-4V sheets and LBM. With the additive process a functional structure is built on top of the bending zone using powder from the same material. As a measure for the connection strength, shear tests were performed. The shear strength is analyzed for both possible process routes of forming and LBM. Therefore a modular clamping device for bent sheets was developed in order to enable simultaneous production of additive parts on several bent sheets with different thicknesses and radii. Results show that the formability of sheets is strongly influenced by the sequence of the process route, while no significant difference in shear strength of the connection was observed, even if the energy density in the LBM process is varied to a large extent. The post heat treatment is discussed as major cause, as homogenization of the microstructure takes place, although the applied temperature is beneath the beta transus temperature.
Keywords: Laser Beam Melting; Additive Manufacturing; Bending; Titanium Alloys

Influence of a bending operation on the bonding strength for hybrid parts made of Ti-6Al-4V - Papke, Thomas; Dubjella, Patrick; Butzhammer, Lorenz; Huber, Florian; Petrunenko, Oleksandra; Klose, Dominik; Schmidt, Michael; Merklein, Marion (Procedia CIRP, 2018)

Influence of Warm Bending on the Surface Topography of Titanium Alloy Ti-6Al-4V - Dubjella, Patrick; Merklein, Marion (Procedia Engineering, 2017)
More frequently industry reverts to titanium alloys such as Ti-6Al-4V for several applications. This is due to its wide range of positive material characteristics like high biocompatibility, good corrosion resistance and high specific strength. Hence, Ti-6Al-4V is utilized for applications in medicine technique, marine and aerospace. However, forming of Ti-6Al-4V at room temperature is limited, which is caused by its hexagonal closed packed (hcp) grain structure. To overcome these limitations it is necessary to form Ti-6Al-4V at elevated temperatures. Thus, further gliding planes are activated and large scaled parts can be formed at low cycle times. Another promising process to generate Ti-6Al-4V structures is additive manufacturing. Via Laser Beam Melting (LBM) geometrical limitations of the forming process can be overcome. Nearly every conceivable geometry like undercuts is possible to generate. However, the process takes comparatively long time and the costs for large batch sizes are high. In order to merge the advantages of forming and LBM a combination of both processes is favorable. The sequence of forming and a subsequent additive process to produce a hybrid part leads to several challenges. Besides forming induced residual stresses in the sheet metal, the topography of the sheet has effect on the bonding quality of sheet metal and additive structure. Especially peaks in roughness may serve as crack initiators. In order to provide suitable parts for the subsequent additive process it is necessary to have a sound knowledge of the impact of the forming operation on the surface topography. For this reason this paper focuses on the investigation of the influence of warm bending on the surface topography of Ti-6Al-4V. Therefore bending tests with varying temperatures, punch radii and different bending angles are conducted and the topography is analyzed with confocal microscopy.
LFT Import::2019-07-29 (2260)
Keywords: Additive Manufacturing; Bending; Titanium

Interaction of Additive Manufacturing and Forming - Merklein, Marion; Dubjella, Patrick; Schaub, Adam; Butzhammer, Lorenz; Schmidt, Michael (Proceedings of 6th International Conference on Additive Technologies, 2016)
Titanium alloys such as Ti-6Al-4V are utilized for a wide range of industrial approaches. This is primarily due to their positive material characteristics such as high biocompatibility, good corrosion resistance and outstanding specific strength. As a result of the hexagonal close packed (hcp) grain structure the achievable plastic deformation of these alloys at room temperature is limited. To overcome these limitations, forming at elevated temperatures is a promising process. A further promising manufacturing method for titanium is laser beam melting (LBM). LBM functions at melted material condition and thereby neglects most manufacturing challenges. It enables to produce individual parts by overcoming geometrical design restrictions compared to conventional manufacturing techniques. Within this work a process chain combining sheet metal forming and laser beam melting is presented and discussed. The main benefit of this combined process is a merge of the positive  characteristics of both manufacturing methods. In former researches deep drawing was used as forming process. Due to inducing a more complex stress level, which is more application oriented, bending will be investigated as a forming strategy for a combination with LBM. Therefore a tool was developed and manufactured. In this study the function of this tool will be described in detail and its qualification for bending flat sheets of Ti-6Al-4V as well as hybrid parts will be researched.
Keywords: Additive Manufacturing; Forming; Bending; Titanium alloys